Development of an SDI service for agricultural scientists in the PCARR network - Galang, Lilia S.; Sison, Josephine C.; Vallejo, Rosa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
SDI (Selctive Dissemination of Information), a personalized type of current awareness service utilizing electronic data processing techniques was explored by means of an operational experiment. The service was made available to a group of fifteen (15) agricultural scientists undertaking research projects funded by the Philippine Council for Agriculture and Resources Research. Questionnaires and interviews were used to gather data on user's in formation requirements thereby initiating profiles.
The database used has been created from the documents contained in AGRIASIA, the computer-produced regional bibliography of the Agricultural Information Bank for Asia, which contain current agricultural literature.
The AGRIS Sytem of classification and indexing principles used in the organization of AGRIASIA references were also employed in describing users' profiles. Document/User profile matching process was achieved through program package called STAIR/VS (Storage And Information Retrieval System/Virtual Storage). Matching was done by using descriptors.
Two (2) computer runs were undertaken. Performance of the SDI system was sought through relevance scores derived from the users' feedback on documents retrieved. A high degree of recall was obtained in the first computer run and precision was achieved in the second computer run. Modifications on the users' profiles increased the efficiency of the system by reducing the amount of non-relevant documents retrieved.
There were four hundred four (404) references retrieved from the AGRIASIA database containing 30, 580 document citations for the fifteen (15) users' profiles.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Agriculture--Documentation--Philippines.; Information storage and retrieval systems--Agriculture.; Philippine Council for Agriculture and Resources Research; Selective dissemination of information